Application of Floating Rice Science and Technology on the Lebak Swamp Land in Agrotourism Tekno 44 Gelebak Dalam Village - Ahmad Sofian; Supli Effendi Rahim; Rosmiah Rosmiah; Iin Siti Aminah; Dessy Tri Astuti; Nurbaiti Amir; Neni Marlina; Maria Lusia (Universitas Muhammadiyah Palembang, 2023)
Tekno 44 Agrotourism is a tourist attraction centered in Gelebak Dalam Village, Rambutan District, Banyuasin Regency, South Sumatra Province. Korem 044 Gapo is in charge of managing this agrotourism with an integrated farming system. Floating rice technology is one way to overcome the problem of flooding that occurs in lowland swamplands. Utilization of Lebak swamp land in South Sumatra for agriculture is still low; rice is only planted once a year during the dry season. The service was carried out from January to February 2023. The methods used included training and assistance regarding the application of floating rice technology on lowland swamp land, as well as facilitating the provision of facilities and infrastructure for the application of floating rice technology. The aim of this service is to increase the knowledge and skills of the Gelembak Dalam Village community regarding the application of floating rice technology on Lebak swamp land. Along with members of Korem 044 Gapo, the residents of Gelebak Dalam Village attended the training and mentoring. The people of Gelebak Dalam Village and members of Korem 044 Gapo are very enthusiastic about participating in training and mentoring to gain new knowledge and skills regarding the application of floating rice technology.